Factors affecting economic growth in Malaysia (2010 -2018) / Harith Rejab - Rejab, Harith (Faculty of Business and Management, 2019)
Economic growth (GDP) plays an important roles to ensure a better position of economic and positive image of a country. The aim of this study is to examine the relationship between inflation, foreign direct investment (FDI), exchange rate, government expenditure, and export on economic growth of Malaysia by using the time series data quarterly basis from 2010 to 2018. This study used secondary data to be run in the E-views software while the models that being used is Multiple Linear Regression to find the relationship between all independent variables and dependent variable. Based on the empirical result, inflation and government expenditure has a positive and significant effect while exchange rate has a positive but insignificant effect on economic growth. Meanwhile export and foreign direct investment (FDI) shows insignificant but has a negative relationship with GDP. Therefore, this study might be useful for policy makers, investors and public.